2001
DOI: 10.1002/aoc.189
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods for the extraction of arsenic compounds from the NRCC standard reference material DORM‐2 and the brown alga Hijiki fuziforme

Abstract: The NRCC standard reference material DORM-2 and the marine brown alga Hijiki fuziforme were extracted with water, methanol/water (9 1), and 1.5 M orthophosphoric acid. The extracts from DORM-2 were analyzed by HPLC-ICP-MS for arsenobetaine, arsenocholine, trimethylarsine oxide, and the tetramethylarsonium cation and the extracts from H. fuziforme for arsenous acid, arsenic acid, dimethylarsinic acid, methylarsonic acid, and four arsenoriboses. Almost no differences between the three extractants were observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…In the case of the marine alga Hijiki fusiforme, the extractability of arsenic compounds increased from 33% with a methanol/water (9/1) mixture to a 74% extraction yield with 1.5 mol l −1 orthophosphoric acid. 11 For the freshwater alga Chlorella vulgaris, the recoveries of total arsenic ranged from 74% for a water extraction to 100% with methanol-water mixtures in which the methanol concentration was above 40% (v/v). A 0.03 mol l −1 phosphate buffer extracted 84% of total arsenic.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the marine alga Hijiki fusiforme, the extractability of arsenic compounds increased from 33% with a methanol/water (9/1) mixture to a 74% extraction yield with 1.5 mol l −1 orthophosphoric acid. 11 For the freshwater alga Chlorella vulgaris, the recoveries of total arsenic ranged from 74% for a water extraction to 100% with methanol-water mixtures in which the methanol concentration was above 40% (v/v). A 0.03 mol l −1 phosphate buffer extracted 84% of total arsenic.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies on the extraction of organoarsenic compounds have been reported. [37][38][39][40][41][42][43][44][45][46] Although the extraction efficiencies were different depends on the matrices and extraction steps involved, most of them reported decent efficiencies between 90-110%. Mechanical shaking, sonication, and pressurized extraction including MW extraction have been used predominantly.…”
Section: Lc-ms Optimization Figure 2(a) and 2(b) Show Typical Ion Chmentioning
confidence: 99%
“…Mixtures of water, water -methanol and methanol -chloroform have been used to establish the best composition for efficiently extracting water-soluble species Hanaoka et al, 2001;Kuehnelt et al, 2001;Brisbin and Caruso, 2002;Geiszinger et al, 2002). As this efficiency depends on the tissue and species to be analysed, the conclusion was reached that all arsenic species in different samples need diverse extraction conditions (Francesconi and Kuehnelt, 2004).…”
Section: Extraction Of the Speciesmentioning
confidence: 99%